Morphological and Stomatal Characteristics of Two Indonesian Local Orchids - Zahara, Meutia; Win, Cho Cho (Journal of Tropical Horticulture, 2019)
Orchids are very famous for their beautiful and long-lasting flowers and variety among the most diverse family of flowering plants in the world, comprising thousand species and hybrids and very attractive. The research aimed to determine the morphological features of two local orchids Phalaenopsis amabilis L. and Dendrobium x Superbiens and the stomatal characteristics of both orchids. Plants were the only living organisms that are able to convert light energy/sunlight into chemical energy, and stomata is an important part of plants for CO2 to enter the leaf and H2O to be released during the photosynthetic reactions. The results showed that Phalenopsis amabilis L. was monopodial orchid and Dendrobium x Superbiensis a sympodial orchid. A qualitative descriptive research method used to describe and interpreted the type of stomata of Phalaenopsis amabilis L and Dendrobium sp. stomatal density were counted on adaxial and abaxial part of the leaf, and the highest stomatal density was obtained on the abaxial part of Dendrobium x Superbiensleaf 290.81 mm-2. The type of stomata was anomocytic for two local orchids.